Oxycodone in the Opioid Epidemic: High ‘Liking’, ‘Wanting’, and Abuse Liability - Kibaly, Cherkaouia; Alderete, Jacob A.; Liu, Steven H.; Nasef, Hazem S.; Law, Ping-Yee; Evans, Christopher J.; Cahill, Catherine M. (Cellular and molecular neurobiology, 2021)
It is estimated that nearly a third of people who abuse drugs started with prescription opioid medicines. Approximately, 11.5 million Americans used prescription drugs recreationally in 2016, and in 2018, 46,802 Americans died as the result of an opioid overdose, including prescription opioids, heroin, and illicitly manufactured fentanyl (National Institutes on Drug Abuse (2020) Opioid Overdose Crisis. https://www.drugabuse.gov/drugs-abuse/opioids/opioid-overdose-crisis . Accessed 06 June 2020). Yet physicians will continue to prescribe oral opioids for moderate-to-severe pain in the absence of alternative therapeutics, underscoring the importance in understanding how drug choice can influence detrimental outcomes. One of the opioid prescription medications that led to this crisis is oxycodone, where misuse of this drug has been rampant. Being one of the most highly prescribed opioid medications for treating moderate-to-severe pain as reflected in the skyrocketed increase in retail sales of 866% between 1997 and 2007, oxycodone was initially suggested to be less addictive than morphine. The false-claimed non-addictive formulation of oxycodone, OxyContin, further contributed to the opioid crisis. Abuse was often carried out by crushing the pills for immediate burst release, typically by nasal insufflation, or by liquefying the pills for intravenous injection. Here, we review oxycodone pharmacology and abuse liability as well as present the hypothesis that oxycodone may exhibit a unique pharmacology that contributes to its high likability and abuse susceptibility. We will discuss various mechanisms that likely contribute to the high abuse rate of oxycodone including clinical drug likability, pharmacokinetics, pharmacodynamics, differences in its actions within mesolimbic reward circuity compared to other opioids, and the possibility of differential molecular and cellular receptor interactions that contribute to its selective effects. We will also discuss marketing strategies and drug difference that likely contributes to the oxycodone opioid use disorders and addiction.